PERANCANGAN RINCIAN KAS TELLER BERBASIS WEB - Salimuddin, Teuku (KITA Institut, 2020)
At the Bank Rakyat Indonesia (BRI) Alue Bilie Unit, the teller cash system experiences difficulties and errors in the teller's cash collection and receipt system and there is an error in the procedure for collecting evidence of cash management (in the form of cash), based on the purpose of the problem referred to the writer conducting research on the Details Website-Based Cash Teller at Bank Rakyat Indonesia (BRI) Unit Alue Bilie. The design of the system used by the Rapid Application Development (RAD) method, a software development process model classified as incremental (multilevel) techniques. RAD emphasizes short, short, and fast development cycles, and data collection techniques using research methods by observation, interview, and literature study. The tools used are web-based fangame using the programming languages PHP, HTML, CSS, JQuery, and MySQL as DBMS. The test results of this application are the systems that are built already meet the needs, the input data process has met the needs and the resulting report has met the needs.Keywords:Details, Cash Teller, Web-based